The answer for the question is y = 3x + 5
Answer:
BC = 22
Step-by-step explanation:
BD = 67
Bc = 3x - 2
CD = 4x + 13
BC + CD = BD (Given)
3x - 2 + 4x + 13 = 67
3x + 4x -2 + 13 = 67
7x + 11 = 67
7x = 67 - 11
7x = 56
x = 56 ÷ 7
x = 8
now instead of x put 8
Bc = 3x - 2
BC = 3(8) -2
BC = 24 -2
BC = 22
Answer:
x=33.4
Step-by-step explanation:
One hundred, if ur teacher asks why say the vertical angle theorem
Answer:
A) x=9/2 B) x=-1/5, 1/2
Step-by-step explanation:
3x-9=27/1-5x
3x-9=27-5x
3x-(-5x)-9=27
3x+5x-9=27
8x-9=27
8x=27+9
8x=36
x=36/8
simplify
x=9/2
Answer: x=9/2
-----------------------------
10x-1/x=3
(10x^2-1)/x=3
10x^2-1=3*x
10x^2-1=3x
10x^2-3x-1=0
factor out the trinomial,
find two numbers that when they multiply,
you get the third term, which is -1 in this case.
When you add those 2 numbers, you get the second term,
which is -3 in this case.
(5x+1)(2x-1)=0
apply the zero property from here,
set 5x+1=0 and 2x-1=0 and solve for x.
5x=0-1=-1, x=-1/5,
2x=0+1=1, 2x=1, x=1/2.
So x=-1/5, 1/2.